Three tiers of sustainability measurement in the grocery retail industry - Vijayan, Gowri (Universiti Putra Malaysia Press, 2016)
The global trend on sustainability has pushed firms to incorporate corporate sustainability into their business operations. This has led to extensive research on sustainability indicators and its application by consultancy firms, organizations, and academicians. However, the primal focus on such studies have always been industries of developed economics with dominating modern formats. This leaves behind the fragmented industries of developing and underdeveloped economies. With globalization and trade policies, such emerging economies are now turning towards sustainability implementation for universal acceptance and sustainable development. It is now imperative for the sustainability researchers to focus on such economies, with their fragmented markets. This chapter gives a summarized view on corporate sustainability and its measurement, highlighting its prevailing limitations for applicability in the fragmented grocery retail industry. Furthermore, the need for a simplified and interpretive evaluation system, for measurement of sustainability across retail formats is discussed. Henceforth, the chapter introduces the Three Tiers Sustainability Ranking System as a possible alternative for sustainability measurement in firms. The Three Tiers Ranking System could be considered as a solution to the wide spread dilemma of sustainability measurement, and performance evaluation based on implementation of practices by the formats. The applicability of the Three Tiers Ranking System, based on similar research paradigms has also been provided for comparative evaluation of the system. This could be the necessary impetus for governments, consultancy firms, and academicians to turn their focus towards sustainable development of fragmented industries.